The effect on critical velocity of runnings with change of direction in soccer - Ari, E.; Cihan, H.; Cetindemir, A. (Baltic Journal of Health and Physical Activity, 2021)
Introduction: The aim of this study was to examine relationships between Yo-Yo intermittent recovery level 1 test (YYIR1T) performance and critical velocity determined by test protocols consisting of runs with a change of direction and straight runs. Material and Methods: Twelve young soccer players voluntarily participated in study (age: 17.07±0.24 years, training experience: 8.42±2.50 years, height: 178.58±5.76 cm, weight: 70.67±6.14 kg, body mass index: 22.16±1.59). To determine critical velocity, 6-, 9- and 12-minute runs were performed with maximum effort on a straight-line running track and a running track with a change of direction. The critical velocity was determined by two linear regression models. YYIR1T was performed to determine players` aerobic endurance. The critical velocity value of the two test tracks was compared by the paired samples T-test. The correlation between test parameters was determined by Spearman`s correlation coefficient. Results: A significant difference between anaerobic distance capacity and the mean running speed of the two test tracks (p<0.05) was found. There was a significant correlation between critical velocity in the straight-line test track and the YYIR1T performance. (p<0.05). Conclusions: Consequently, it might be said that runs with a change of direction might increase energy expenditure and anaerobic distance capacity was highly affected by those compared to critical velocity.